Oczekiwania praktyki gospodarczej wobec oferty szkół wyższych - Haberla, Marcin (Teaching Program to Meet the Demands of Business, 2007)
After a few years of social and economic transformations, Poland still has not created a satisfactory education system. In such a transformed reality, higher levels of education should meet the changes that are taking place in the economy, sometimes even overtake them. It is important to create a correlation between universities - their educational and experts offer and market expectations. The article presents possibilities for joint work between different economic entities and colleges. Those chances are just an example - not a formula for success. But these possibilities could help reach social and economic progress, as well as development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (3); 2007; nr 1171, s. 31-43